2016
DOI: 10.1002/hep.28598
|View full text |Cite
|
Sign up to set email alerts
|

Nonabsorbable disaccharides for hepatic encephalopathy: A systematic review and meta‐analysis

Abstract: NADs have beneficial effects in the treatment and prevention of HE; their use, in this context, confers additional benefits including a reduction in serious liver-related morbidities and all-cause mortality. (Hepatology 2016;64:908-922).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(65 citation statements)
references
References 44 publications
0
54
0
11
Order By: Relevance
“…The major difficulty with these approaches is that they do not provide point diagnostic information and thus are not of value to clinicians who need to decide whether to treat a patient for HE at a given point in time; given the low toxicity of treatments prescribed for HE [4], it is hardly operational to wait for longitudinal data to see if the patient truly has HE or whether they may develop HE at some point in the future. As an alternative we would advocate retention of normative thresholds.…”
Section: To the Editormentioning
confidence: 99%
“…The major difficulty with these approaches is that they do not provide point diagnostic information and thus are not of value to clinicians who need to decide whether to treat a patient for HE at a given point in time; given the low toxicity of treatments prescribed for HE [4], it is hardly operational to wait for longitudinal data to see if the patient truly has HE or whether they may develop HE at some point in the future. As an alternative we would advocate retention of normative thresholds.…”
Section: To the Editormentioning
confidence: 99%
“…A systematic metaanalysis has shown nonabsorbable disaccharides to be useful in the treatment and prevention of HE. 20 Lactulose is useful in the treatment of HE. Studies have established its role in primary as well as secondary prophylaxis of overt HE.…”
Section: Ejohgmentioning
confidence: 99%
“…Lactulose can significantly lower ammonia levels and has served as the primary therapy for HE. A systematic review involved 38 randomized controlled trials (RCTs) and evaluated the effects of the non‐absorbable disaccharides (NADs), showing that NADs had a beneficial effect on overt HE (OHE) episodes, secondary prophylaxis and primary prophylaxis for preventing the development of HE . Lactulose, in studies primarily from India, has shown a beneficial impact on MHE reversal and on quality of life (QoL) .…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review involved 38 randomized controlled trials (RCTs) and evaluated the effects of the nonabsorbable disaccharides (NADs), showing that NADs had a beneficial effect on overt HE (OHE) episodes, secondary prophylaxis and primary prophylaxis for preventing the development of HE. 11 Lactulose, in studies primarily from India, has shown a beneficial impact on MHE reversal and on quality of life (QoL). 12 Further, Bajaj et al 8 and Sarangi et al 13 proved that NADs can beneficially affect microbiota composition.…”
mentioning
confidence: 99%